Two new species of Halacarus (Acari, Prostigmata) from Brazil - Pepato, Almir R. (Zootaxa, 2013)
The genus Halacarus is recorded from the Brazilian littoral for the first time. Two new species are described. Halacarus omului sp. nov., obtained from algae on the intertidal or immediate subtidal, is a member of the actenos species group and can be distinguished from most congeners by having fifth and sixth pairs of dorsal setae immediately adjacent to fourth and fifth pairs of gland pores, on same minute sclerite. Halacarus todaroi sp. nov. was obtained from sublittoral coarse sand and shell debris and can be distinguished from most congeners by lacking sexually dimorphic dorsal plates, the pres-ence of the posterior dorsal plate, although it does not bear the fourth pair of gland pores, and the presence of ocular plates as a small platelet bearing the pore canaliculi. Further diagnoses are provided along with the species descriptions.